2020
DOI: 10.1101/2020.05.11.088278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural variants at theBRCA1/2loci are a common source of homologous repair deficiency in high grade serous ovarian carcinoma

Abstract: Around half of high grade serous ovarian carcinomas (HGSOC) show homologous recombination repair deficiency (HRD), often caused by germline or somatic single nucleotide variant (SNV) mutations or small indels disrupting BRCA1/2. We have uniformly processed the largest collection of whole genome sequencing (WGS) data from HGSOC samples to date (N=205), comprehensively characterising the somatic mutational landscape, and expression at the BRCA1/2 loci. We discover that large structural variants (SV) are a freque… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…If sWGS is to be developed for use in clinical trials, it will be imperative to establish robust criteria for sequencing depth, especially in low cellularity samples or small core biopsies. We also did not perform whole exome sequencing or deep WGS, so are unable to comment upon small variants (SNV, indel) beyond our targeted panel nor on larger scale rearrangements (12,41).…”
Section: Discussionmentioning
confidence: 99%
“…If sWGS is to be developed for use in clinical trials, it will be imperative to establish robust criteria for sequencing depth, especially in low cellularity samples or small core biopsies. We also did not perform whole exome sequencing or deep WGS, so are unable to comment upon small variants (SNV, indel) beyond our targeted panel nor on larger scale rearrangements (12,41).…”
Section: Discussionmentioning
confidence: 99%
“…(B) Diagnosis: the stratification of low‐grade gliomas (isocitrate dehydrogenase [IDH] mutant gliomas) has recently been updated by the WHO to include those with or without concurrent 1p and 19q co‐deletion [161]. (C) Treatment targets: tumours with large deletions of both BRCA1 and BRCA2 loci form a subset of HR‐deficient tumours that are exquisitely sensitive to PARP inhibitors [154,155,162]. (D) Treatment response: Mansfield et al [157,158] demonstrated that malignant mesothelioma harbours neoantigens that are generated by complex SVs, and that their generation was associated with the clonal expansion of T cells, indicating that complex SV burden can be used to predict response to immune checkpoint inhibitors.…”
Section: The Emerging Clinical Applications Of Svs In Cancermentioning
confidence: 99%
“…Lastly, SVs do not always promote tumour development, and in fact can be deleterious to the tumour. For example, deletions of BRCA1/2 leads to DNA damage repair deficiencies in certain tumours [155,156], and tumours with a large fraction of complex SVs generate vast amounts of neoantigens that may confer susceptibility to immune therapies [157,158].…”
Section: The Functional Impacts Of Structural Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…At the gene sequence level, the identification of mutational disruption in BRCA1 and BRCA2 (BRCA1/2m) has ultimately paved the way for the integration of poly-(ADP-ribose) polymerase (PARP) inhibitor use into routine care for some patients (8)(9)(10). Indeed, there continues to be an intense research effort surrounding mechanisms and implications of homologous recombination DNA repair (HRR) disruption beyond BRCA1/2m (11); these include mutation of non-BRCA1/2 HRR genes (12), large-scale genomic variants disrupting BRCA1/2 (13), epigenetic inactivation of HRR players such as BRCA1 and RAD51C (5,14), and overexpression of the BRCA2 regulator EMSY (15,16).…”
Section: Introductionmentioning
confidence: 99%